Contamination of Heavy Metal(Loid)S in Cereals, Vegetables, and Legumes Purchased from Local Markets of Jiaozuo, China and The Associated Health Risk Assessment - Wu, Zhen (International Journal of Natural Resources and Environmental Studies, 2024)
The health implications associated with the consumption of food contaminated by heavy metals (HMs) and metalloids, specifically arsenic (As), remain a global concern. This study aimed to investigate the occurrence of HMs and As in various food categories, including cereals (rice, wheat, and corn), vegetables (leafy greens, edible mushrooms, kale, solanaceous fruits, and tubers), and legumes (peanuts, soybeans, and mung beans), commercially available in Jiaozuo city. Additionally, we sought to assess the potential health risks posed to human consumers by the ingestion of these three food categories. To evaluate the extent of contamination, both single-factor analysis and Nemerow’s synthetical pollution index were employed. The assessment of health risks was conducted using the health risk model recommended by the United States Environmental Protection Agency. Specifically, cereals exhibited exceedance rates of 2.60% for Cr, 44.16% for Hg, 3.90% for Ni and 3.90% for Pb. Notably, vegetable samples exhibited exceedance rates of 0.90% for Hg and 17.12% for Zn. Among legume samples, exceedance rates were 16.98% for Cr, 75.47% for Ni and 13.21% for Pb, while other HMs and As remained within standard limits. The cumulative contamination level of HMs in each diet category ranked in the order of legumes > cereals > vegetables. Based on the daily intake of cereals, legumes and vegetables, the Total Target Hazard Quotient for HMs in both children and adults exceeded a value of 1, indicating the potential noncarcinogenic risks (non-CRs) associated with consumption of these three dietary categories. Conversely, the CR induced by HMs through the consumption of these foods remained within acceptable levels for both children (8.92×10-6) and adults (2.65×10-6). It is noteworthy that the health risk posed by HMs through food consumption was more pronounced in children than in adults.